2017
DOI: 10.3390/met7080297
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Structure and Mechanical Properties of Pure Titanium Produced by Rotary-Die Equal-Channel Angular Pressing

Abstract: Pure titanium was efficiently processed up to four passes at 420 • C by rotary-die equal-channel angular pressing (RD-ECAP). The deformation structure and mechanical properties of pure titanium with various RD-ECAP passes were subsequently investigated. Microstructure evolution revealed that plastic deformation was accommodated mainly by twins during the first and second passes, while the predominant deformation mechanism was dislocation slip during the third and fourth passes. {1012} twins were detected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…It has a good level of microstructural homogeneity also confirmed by Figure 9 but it has not an ideal homogenous structure, the existence of some parallel shear bands, indistinguishable cell boundaries and high dislocation density regions which is apparent from color differences in the interior section of grains are some slight traces of microstructural heterogeneity. The occurrence of mixture structural phenomena including shear bands, elongated and equiaxed grains and substructures in four-passed ECAE Ti and SPDed Ti also was shown in previous studies [12,45,46]. It was shown that annealing in the temperature range of 400-450°C for half an hour could lead to microstructural homogeneity [34].…”
Section: Annealedsupporting
confidence: 66%
“…It has a good level of microstructural homogeneity also confirmed by Figure 9 but it has not an ideal homogenous structure, the existence of some parallel shear bands, indistinguishable cell boundaries and high dislocation density regions which is apparent from color differences in the interior section of grains are some slight traces of microstructural heterogeneity. The occurrence of mixture structural phenomena including shear bands, elongated and equiaxed grains and substructures in four-passed ECAE Ti and SPDed Ti also was shown in previous studies [12,45,46]. It was shown that annealing in the temperature range of 400-450°C for half an hour could lead to microstructural homogeneity [34].…”
Section: Annealedsupporting
confidence: 66%
“…This level of consideration is missing in model [ 12 ] and, more generally, in the models based on the homogenization approach, and will present a challenge for future investigations. It is particularly interesting in view of the recent technological developments which show a tendency to fabricate Ti and Ti alloys with complex microstructures containing micro- and nano-size elements, e.g., submicron grains [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Zhao et al [22] revealed that the microstructure of titanium processed by one-pass of ECAP at RT is characterised by a high density of {10 12} twinning. After the first pass of ECAP, Chen et al [147] observed both {10 11} and {10 12} twins in the microstructure of CP titanium processed at 450 • C. Gu et al [148] ECAPed titanium at 420 • C and detected {10 12} twins after the first pass and {10 11} twins after the second pass. Moreover, they revealed that the dislocation slip is the main deformation mechanism when processing titanium with third and fourth passes of ECAP.…”
Section: Twinning Of Titanium Due To Ecapmentioning
confidence: 99%